2004
DOI: 10.1029/2003ja010130
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing of possible plasma density bubbles in the inner Jovian dayside magnetosphere

Abstract: During the 2001 Cassini encounter with Jupiter, the Radio and Plasma Wave Science (RPWS) instrument detected fine spectral and temporal structure with broadband kilometric radiation. Applying known electron cyclotron harmonic radiation models, this microstructure is interpreted as originating from a plasma density depletion or bubble at the edge of the Io torus. The microstructure became very complicated at the event beginning and end (formation of broadband bursty structures), and this is interpreted as origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Reiner et al (2000) have found that nKOM events were detected by Ulysses/URAP after a few rotations of Jupiter following strong solar wind ram pressure pulses, and that there was a clear 26 days cadence of nKOM observations. Farrell et al (2004) have interpreted a Jovian broadband kilometric radiation (bKOM) as an Electron–Cyclotron Harmonic radiation originating from a plasma density depletion or plasma bubble at the outer edge of the Io torus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reiner et al (2000) have found that nKOM events were detected by Ulysses/URAP after a few rotations of Jupiter following strong solar wind ram pressure pulses, and that there was a clear 26 days cadence of nKOM observations. Farrell et al (2004) have interpreted a Jovian broadband kilometric radiation (bKOM) as an Electron–Cyclotron Harmonic radiation originating from a plasma density depletion or plasma bubble at the outer edge of the Io torus.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Kaiser and MacDowall (1998) have shown that “bullseyes” emission have a tendency to occur after the passage of a solar wind pressure pulse, which crosses the Jovian magnetosphere every 13 or 26 days and the temporal spacing between the centers of the individual “bullseyes” was 6% longer than the Jupiter rotation. Farrell et al (2004) have proposed that “bullseyes” emission can be explained (non-uniquely) as typically nKOM emissions from the radially extended plasma fingers developed in the course of the strong interchange instability which may operate along the outer Io torus edge (Yang et al, 1992, 1994). This instability, which in general can be considered as a competition between cold and energetic plasma components, can be triggered by the strong solar wind impulses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the well known S-bursts, drifting tones and spectral bands were observed within bKOM Lecacheux et al, 2001). A tentative interpretation of the latter in association with plasma density bubbles in the inner jovian dayside magnetosphere was proposed by Farrell et al (2004a).…”
Section: Rpws Observations At Jupitermentioning
confidence: 97%
“…Furthermore, several episodes have been found when periodic non-Io DAM was observed simultaneously with so-called "bullseyes", U-shaped narrowband emissions in the low frequency 20-50 kHz band (Kaiser and MacDowall, 1998), observed by Ulysses/URAP spacecraft. Farrell et al (2004) explained the "bullseyes" emission as Jovian narrowband kilometric emissions (nKOM) generated in the radially extended plasma fingers developed in the course of the interchange instability in the Io torus. These latitudinal extended fingers may be a plasma source which supplies the cyclotron maser in the auroral region.…”
Section: Jupiter Radio Emissionmentioning
confidence: 99%